Theater – Where Worlds Converge and a Window into the Romani Soul. Introduction to the Photo Supplement - Berkyová, Renata (Romano džaniben, 2025)
This text serves as an introduction to a photographic supplement documenting contemporary Romani theater in the Czech Republic over the past decade. Through selected productions and projects, it illustrates how Romani theater bridges professional and community practices, reflects historical memory and current social issues, and creates a space for sharing experiences and engaging in dialogue with the audience. Special attention is given to the Theater of the Oppressed and the growing involvement of Romani artists on established stages, which contributes to greater visibility of Romani perspectives and to the development of theater as a tool for social change, empathy, and critical reflection.
Keywords: Roma theatre; community art; Theatre of the Oppressed; Roma communities; cultural representation; social issues; audience participation; identity and memory